Артикуляция соционима «сарариман» - Райхерт, К. В.; Rayhert, K. V. (My University, 2017)
Соционим «сарариман» был придуман в 1916 г. или 1918 г. японским художником Ракутэном Китадзавой для обозначения новой социальной, культурной и экономической группы «белых воротничков», которые изначально назывались «йофуку саймин» и «цутомэнин» и были результатом слияния военной идеологии самураев с западным образованием в ходе реализации проекта модернизации Японии, известного под названием «Реставрация Мейдзи». После Второй мировой войны сарариман стал символом коммерческого технонационализма, который является трансформированным военным технонационализмом, возникшим в ходе «Реставрации Мейдзи». Поэтому в какой-то степени сарариман может быть понят как пережиток милитаризованного прошлого Японии, что, возможно, является причиной современного экономического кризиса национальной системы страны, образовавшейся вокруг института сараримана. Возможным выходом из ситуации, сложившейся в современной национальной системе Японии на основе института сараримана, может быть либо полный отказ от института сараримана (и коммерческого технонационализма), либо же наделение новыми значениями и смыслами понятия «сарариман», феномена и института, стоящих за этим понятием.

Соціонім «сараріман» був вигаданий у 1916 або 1918 році японським художником Ракутеном Кітадзавою для позначення нової соціальної, культурної й економічної групи «білих комірців», які первісно називалися «йофуку саймін» і «цутоменін» і були результатом злиття військової ідеології самураїв із західною освітою під час реалізації проекту модернізації, відомого як «Реставрація Мейдзі». Після Другої світової війни сараріман став символом комерційного технонаціоналізму, який є перетвореним військовим технонаціоналізмом, що виник під час «Реставрації Мейдзі». Тому певною мірою сарарімана можна розглядати як пережиток мілітаризованого минулого Японії, що, можливо, є причиною сучасної економічної кризи національної системи країни, утвореної навколо інституту сарарімана. Можливим розв’язання кризи може бути або цілковита відмова від інституту сарарімана (та комерційного технонаціоналізму), або наділення новими значеннями та смислами поняття «сараріман», феномену й інституту, що стоять за цим поняттям.

Socionym “sararyman” was coined in 1916 or 1918 by Japanese artist Rakuten Kitazawa for collective naming of new social, cultural and economic group of the “white collar” workers who were named “yofuku saimin” and “tsutomenin” originally and who were the results of the merge of the military ideology of the Samurai and the Western Education during the realization of the project of modernization of Japan known as “The Meiji Restoration”. After World War II the sararyman became a symbol of the commercial techno-nationalism that was a transformed military techno-nationalism originated from “The Meiji Restoration”. There fore, in some way the sararyman can be understood as a remnant of the military past of Japan what, probably, can be seen as a cause for the contemporary economic crisis of the national system of Japan aroused around the sararyman institute. The possible solution of the crisis can be either a full rejection of the sararyman institute and the commercial tech- no-nationalism or an investment of new meanings to the socionym of sararyman and to the phenomenon and institute of the sararyman.

Socionym “sararyman” was coined in 1916 or 1918 by Japanese artist Rakuten Kitazawa for collective naming of new social, cultural and economic group of the “white collar” workers who were named “yofuku saimin” and “tsutomenin” originally and who were the results of the merge of the military ideology of the Samurai and the Western Education during the realization of the project of modernization of Japan known as “The Meiji Restoration”. After World War II the sararyman became a symbol of the commercial techno-nationalism that was a transformed military techno-nationalism originated from “The Meiji Restoration”. There fore, in some way the sararyman can be understood as a remnant of the military past of Japan what, probably, can be seen as a cause for the contemporary economic crisis of the national system of Japan aroused around the sararyman institute. The possible solution of the crisis can be either a full rejection of the sararyman institute and the commercial tech- no-nationalism or an investment of new meanings to the socionym of sararyman and to the phenomenon and institute of the sararyman.
Райхерт К. В. Артикуляция соционима «сарариман» / К. В. Райхерт // Актуальні проблеми філософії та соціології: Науково-практичний журнал / Голов. ред. Д. В. Яковлев; відпов. секретар І. В. Шамша; Міністерство освіти і науки України; Національний університет "Одеська юридична академія". - Одеса, 2017. - Вип. 19. - С. 77-80.
Keywords: артикуляция; самурай; соционим; технонационализм; Япония; артикуляція; самурай; соціонім; технонаціоналізм; Японія; articulation; Japan; Samurai; socionym; techno-nationalism